A 12-year-old girl with poliosis. - Milano, A. (European Journal of Pediatric Dermatology, 2017)
When we collected the story of the patient we thought about the most common diagnosis of halo nevus with leukotrichia of the scalp. However, doubts arose when, collecting the family history, the mother told us to have a LAM. Isolated or associated with tuberous sclerosis this is a rare disease occurring almost exclusively in pre-menopausal females; LAM Is characterized by an abnormal proliferation of smooth muscle cells expressing the estrogenic receptors; it usually involves the lungs with cystic destruction of pulmonary parenchyma, the lymphatic vessels of the chest and abdomen and the kidneys. We considered the possibility that the white hair could be an expression of tuberous sclerosis: this sign is really present in 60% of cases of tuberous sclerosis (1), and may sometimes represent the sign of disease initiation (2). The lack of tuberous sclerosis signs and the other halo nevi led to the right diagnosis.